2023
DOI: 10.1177/15910199231196451
|View full text |Cite
|
Sign up to set email alerts
|

The effect of occlusion location and technique in mechanical thrombectomy for minor stroke

Isaac Josh Abecassis,
Eyad Almallouhi,
Reda M. Chalhoub
et al.

Abstract: Introduction Endovascular mechanical thrombectomy (MT) is an established treatment for large vessel occlusion strokes with a National Institutes of Health Stroke Scale (NIHSS) score of 6 or higher. Data pertaining to minor strokes, medium, or distal vessel occlusions, and most effective MT technique is limited and controversial. Methods A multicenter retrospective study of all patients treated with MT presenting with NIHSS score of 5 or less at 29 comprehensive stroke centers. The cohort was dichotomized based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…A total of 7,320 patients from 16 (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) studies (1 randomised controlled trial and 15 observational studies) were enrolled in this study, including 3,406 with combined stent retriever and contact aspiration and 3,914 with stenting alone. The characteristics of the demographics regarding the type of literature included in the study are shown in Table 1.…”
Section: Basic Characteristics Of the Research Objectmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 7,320 patients from 16 (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) studies (1 randomised controlled trial and 15 observational studies) were enrolled in this study, including 3,406 with combined stent retriever and contact aspiration and 3,914 with stenting alone. The characteristics of the demographics regarding the type of literature included in the study are shown in Table 1.…”
Section: Basic Characteristics Of the Research Objectmentioning
confidence: 99%
“…In terms of 90-day good functional prognosis, a total of 10 papers were included (12,13,15,17,(19)(20)(21)(22)(23)25) with high heterogeneity (I 2 = 69%, p = 0.0007). Use of random effects models.…”
Section: Mrs 0-2 Within 90 Daysmentioning
confidence: 99%
See 1 more Smart Citation